Increasing efficiency of preterm birth prediction - Korovai , Serhiy; Lakhno, Igor (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2021)
Abstract. The disturbed placentation in a certain way plays an important role in the pathogenesis of great obstetric syndromes. Therefore, the possibility of using biochemical indicators of the level of placental growth factor (PlGF) and fms-like tyrosine kinase (sFlt-1) for predicting preterm labor is of great interest. The aim of the study was developing criteria for predicting preterm labor based on the combined use of ultrasound cervicometry and the concentration of PlGF and sFlt-1. Materials and methods. A total of 227 pregnant women were examined, 190 of whom had preterm birth. Group I included 48 women whose pregnancy completed at 23 to 27 weeks. In group II, 142 women with prematurity in terms of 28 to 36 weeks were observed. Group III included 37 women with a healthy pregnancy, which completed at 38–41 weeks. All patients involved in the study underwent ultrasound cervicometry on a Voluson 730 (GE Healthcare, USA) at 16 weeks, and also the concentration of PlGF and sFlt-1 in blood serum by electrochemiluminescence immunoassay using a Cobas e411 analyzer was studied (Roche diagnostics, Switzerland). Results. The study revealed a significant (p < 0.001) decrease in the average concentration of PlGF in the blood serum by 65 % associated with an increased level of sFlt-1 by 93% in women with early termination of pregnancy – 23–27 weeks (group I) in relation to women with a healthy pregnancy. In women with preterm birth at 28–36 weeks of gestation (group II), a similar trend of changes was observed: the PlGF level significantly (p = 0.014) decreased on average by 68 % in relation to women with a healthy pregnancy. In women of group I, the value of the sFlt-1 / PlGF ratio exceeded (p < 0.001) the values of patients in group III by 14 times. But an even more pronounced imbalance of angiogenic factors was observed in women of group II – on average 16 times. Two main markers were used to predict premature birth: shortening of the cervix according to ultrasound cervicometry data of less than 30 mm, as well as the sFlt-1/PlGF ratio of more than 50 conv. units. The odds ratio (OR) of preterm birth in the case of using only the length of the cervix was 34,133 (95 % confidence interval – 12.308–94.660). OR in the case of combined use of cervicometry data and angiogenesis variables was 148.750 (95 % confidence interval – 33.243–665.593). Conclusion. Thus, the use of an additional biochemical marker significantly improved the accuracy of preterm labor prediction.